Glucolysis in Pseudomonas putida: Physiological Role of Alternative Routes from the Analysis of Defective Mutants - Vicente, M. (1973)
A number of mutants in which glucolysis is impaired have been isolated from Pseudomonas putida. The study of their behavior shows that this organism possesses a single glucolytic pathway with physiological significance. The first step of the pathway consists in the oxidation of glucose into gluconate. Two proteins with glucose dehydrogenase activity appear to exist in P. putida but the reasons for this duplicity are not clear. The process continues with the formation of 2-ketogluconate which is in turn converted into gluconate-6-phosphate. This is proved by the fact that mutants unable to form gluconate-6-phosphate from 2-ketogluconate show extremely slow growth on glucose or gluconate (generation times are increased more than 100 times). Other possible routes for the conversion of glucose into gluconate-6-phosphate, the glucose-6-phosphate pathway, or the direct phosphorylation of the gluconate formed by glucose oxidation are only minor shunts in P. putida. The Entner-Doudoroff enzymes, which catalyze the conversion of gluconate-6-phosphate into pyruvate and triosephosphate, appear to be essential to grow on glucose and also on gluconate and 2-ketogluconate. A significative role of the pentose route in the catabolism of these substrates is not apparent from this study. In contrast, P. putida strains showing no activity of the Entner-Doudoroff enzymes grow readily on fructose, although there is evidence that this hexose is at least partially catabolized via gluconate-6-phosphate.